The Drifting of Baptist Youths to Other Denominations in Delta State: Causes and Panacea - Ottuh, John Arierhi (Advances in Social Sciences Research Journal, 2015)
The research examined causes and panacea of the drifting of Baptist youths to other church denominations in Delta State. Moreover, the main aim of the study was to sensitize the Baptist youth of the need to remain in the Baptist church. In order to achieve this, the survey research method was explored as a methodology. Questionnaires were used to sample opinion of Baptist youths in Delta State using the cluster sampling methods in some cities and towns of Delta State. The research showed that some Baptist youths in Delta State were gradually drifting to other church denominations like the Pentecostal church and that this is happening more in the campus due to lack of strong Baptist campus ministries in tertiary institutions. However, lack of constant willingness for economic empowerment, insensitivity of the church leadership to youth’s spiritual and physical needs were also identified as the causes of the drift. Due to the problems that have been identified, this research work recommended that establishment of strong campus ministries, bridging the gap between the ancient and modern in the Baptist church and positive branding of the Baptist church by members especially parents could be helpful in tackling the problem of Baptist youth’s drifts to other church denominations. This work was concluded on the presupposition that when all the tiers of Baptist leadership and memberships in Nigeria, especially in Delta State see the drift of the Baptist youths as a challenge that calls for: prayers, training and retraining through discipleship programmes, more radical campus Baptist youth ministries and the drifting youths to believe Baptist biblical practices and retracing their steps, the problem will be surmounted by the Baptist family.